Aplikasi Pembelajaran Bahasa Dayak Ngaju Berbasis Web - Yandi Laurensa; Alexander Setiawan; Kristo Radion Purba (Jurnal Infra, 2017)
Indonesia is a rich country in cultural heritage, one of the cultural heritage is a very large number of regional languages. Of the many regional languages in Indonesia there is Dayak Ngaju language, which commonly used by the people of Central Kalimantan. Now Dayak Ngaju language began to be rarely used and studied by the young generation, resulting in many people who cannot speak the native language of their own region. Dayak Ngaju language learning has been integrated in “Muatan Lokal” subjects in elementary schools which are given only 1 to 2 hours per week. This allocation is not enough to learn the Dayak Ngaju language.Based on background issues, will be designed a Dayak Ngaju language learning application through web technology using PHP as programming language and MySQL as database server.Results obtained from applications that have been made, the application has been able to display Dayak Ngaju Language learning information that is quite complete and can be accessed well by the user. From questioner, 70% of users stated that the features in the application made are considered good as a medium of Dayak Ngaju language learning, while the remaining 30% rate is enough.